Unmanned Aerial Vehicle Using AI-ML - Soham Suryawanshi; Bhoomi Patil; Rohit Walia; Ruturaj Shingte (International Journal of Satellite Remote Sensing, 2025)
Remotely piloted aircraft systems (RPAS), commonly known as drones, have evolved significantly in recent years, revolutionizing various industries and domains. This article provides an overview of the key aspects of RPAS technology, their applications, and the impact they have had on society. RPAS are autonomous or semi-autonomous aerial vehicles that can be controlled remotely, offering diverse capabilities, from data collection and surveillance to cargo delivery and recreational activities. This abstract discusses the technical components of RPAS, including sensors, communication systems, and control mechanisms, emphasizing the role of artificial intelligence and advanced software in enhancing their functionality. Furthermore, it explores the wide-ranging applications of RPAS in agriculture, environmental monitoring, disaster management, filmmaking, and infrastructure inspection, among others. The abstract also highlights the regulatory challenges and ethical considerations associated with the proliferation of RPAS. As RPAS continue to advance and become more accessible, it is crucial to strike a balance between their numerous benefits and the need for responsible and safe usage. This article underscores the transformative potential of RPAS in various fields and encourages further research and innovation in this rapidly evolving technology.
Keywords: Agriculture; Artificial Intelligence (AI); Remotely piloted aircraft systems (RPAS); cargo; sensors